Making Evil: The Science Behind Humanity's Dark Side - Julia Shaw (Canongate, 2019)
Are you evil? A smart and highly readable exploration of why we think and do bad things. Dr Julia Shaw shows us that the same dispositions that make us capable of heinous crimes may also work to our advantage. And, if evil is within all of us, should it be said to exist at all? In Making Evil, Shaw uses a compelling mix of science, popular culture and real life examples to break down timely and important issues. How similar is your brain to a psychopath's? How many people have murder fantasies? Can A.I. be evil? Do your sexual proclivities make you a bad person? Who becomes a terrorist? This is a wide-ranging exploration into a fascinating, darkly compelling subject.